Geography and the water–energy–food nexus: Introduction. Issue 4 (5th November 2019) - Scott, Marian; Larkin, Alice
Abstract : This themed section was initiated after the 2016 Annual Conference of the Royal Geographical Society‐Institute of British Geographers, which had the overall theme of Nexus Thinking, and which included assessment of geographical dimensions of the water–energy–food (WEF) nexus. In this short editorial introduction, we outline the context for this assessment, and introduce the particular focus of the four papers that make up the section. We then show how they add to our understanding of the nexus in terms of the multiple and inter‐dependent geographical scales at which the WEF nexus can be analysed, and be the subject of governance, policy and action. Abstract : In this short editorial introduction, we outline the context for debates around the water–energy−food nexus in geography. We then introduce the focus of the four papers in this themed collection, and show how together, they add to our understanding of the nexus from a variety of perspectives.